Respiratory Syncytial Virus Nonstructural Protein 1 Promotes 5-Lipoxygenase via miR-19a-3p - Mei Zheng; Panpan Fan; Pu Yang; Junwen Zheng; Dongchi Zhao (Journal of Immunology Research)
Background. Respiratory syncytial virus (RSV) infection can regulate the expression of a wide range of noncoding microRNAs (miRNAs), in which mir-19a-3p can participate in airway inflammatory response by regulating 5-lipoxygenase (5-LO) pathway. RSV nonstructural protein (NS) 1 is involved in the airway hyperresponsiveness during RSV infection. Methods. The expression levels of miR-19a-3p and inflammatory signaling-related indicators were detected using quantitative real-time PCR and western blot analyses on the A549 cells transfected with NS1 expression plasmids (pNS1). The 5-LO-mediated inflammatory signaling pathway was assessed when the miR-19a-3p or 5-LO was inhibited. Results. The immunofluorescence analysis showed that the plasmid-mediated NS1 protein was observed in both the cytoplasm and nucleus. The expression level of miR-19a-3p was significantly upregulated in the pNS1 or RSV-treated cells, which was reversed by the NS1 small interfering RNA. In addition, pNS1 also upregulated the expression of 5-LO, interleukin-5 (IL-5), and leukotriene B4 (LTB4), which was also significantly inhibited by the miR-19a-3p antagonists. The 5-LO inhibitor MK886 prevented the increase in the expression level of IL-5 induced by pNS1. Conclusions. These results suggested that the RSV NS1 might play an important role in the pathogenesis of RSV by activating the 5-LO and subsequent inflammatory cytokines through miR-19a-3p.